"Attending to History" in Major System Change in Healthcare in England: Specialist Cancer Surgery Service Reconfiguration - Catherine Perry; Ruth J. Boaden; Georgia B. Black; Caroline S. Clarke; Sarah Darley; Angus I.G. Ramsay; David C. Shackley; Cecilia Vindrola-Padros; Naomi J. Fulop (Kerman University of Medical Sciences, 2022)
Background  The reconfiguration of specialist hospital services, with service provision concentrated in a reduced number of sites, is one example of major system change (MSC) for which there is evidence of improved patient outcomes. This paper explores the reconfiguration of specialist oesophago-gastric (OG) cancer surgery services in a large urban area of England (Greater Manchester, GM), with a focus on the role of history in this change process and how reconfiguration was achieved after previous failed attempts.Methods  This study draws on qualitative research from a mixed-methods evaluation of the reconfiguration of specialist cancer surgery services in GM. Forty-six interviews with relevant stakeholders were carried out, along with ~160 hours of observations at meetings and the acquisition of ~300 pertinent documents. Thematic analysis using deductive and inductive approaches was undertaken, guided by a framework of 'simple rules' for MSC.Results  Through an awareness of, and attention to, history, leaders developed a change process which took into account previous unsuccessful reconfiguration attempts, enabling them to reduce the impact of potentially challenging issues. Interviewees described attending to issues involving competition between provider sites, change leadership, engagement with stakeholders, and the need for a process of change resilient to challenge.Conclusion  Recognition of, and response to, history, using a range of perspectives, enabled this reconfiguration. Particularly important was the way in which history influenced and informed other aspects of the change process and the influence of stakeholder power. This study provides further learning about MSC and the need for a range of perspectives to enable understanding. It shows how learning from history can be used to enable successful change.